Optimasi Penempatan Electronic Data Capture (EDC) Berbasis Drive Test 3G di Gedung Pusat Perbelanjaan - Andari Dyah Widowatie (Politeknik Negeri Malang, 2018)
The problem that often occurs in malls or supermarkets is the use of EDC as a non-cash payment tool for alternative customers. However, the use of EDC machines sometimes experiences problems, namely when customers enter data so that transactions take longer, so this study aims to analyze the optimization of EDC placement in shopping center buildings. This research method is to measure the parameters, namely the RSCP and the closest antenna coverage from the EDC. In this study, three samples were taken, namely Cassa 1, 2 and 3 at Matahari Department Store Malang Town Square. The results of this study were obtained that the Drive Test in the Matahari room showed that Cassa-1, Cassa-2 and Cassa-3 received RSCP with green color which means good. Two of the three tools, namely Drive Test and Mobile can display RSCP with a value that is not too much difference. Especially for EDC is only able to visually display the RSCP and the results of previous calculations, the value of ten antennas which is in the Matahari room has a coverage area below 10 m. And the UG-12 antenna, which is the closest antenna to Cassa-3, that is outside the antenna coverage, while the UG-08 antenna can still reach the Cassa-3 area. This shows that the placement of EDC has met the requirements to get adequate signal quality and the position of the Cassa table can be moved according to the antenna coverage calculation on the Link budget and Path Loss calculations